Carlos Quintáns Eiras, Antonio Raya y Cristóbal Crespo : Piscina en Laracha, A Coruña - Baldellou, Miguel Angel (2000)
Pileta cubierta construída en hormigón como material base y madera
Keywords: MADERA; MATERIALES DE CONSTRUCCION; HORMIGON; ESPAÑA; LA CORUÑA; PILETAS DE NATACION CUBIERTAS; QUINTÁNS EIRAS, CARLOS; RAYA, ANTONIO; CRESPO, CRISTÓBAL